10 Significants variables of academic success - Liliana BUJOR (Association of Social and Educational Innovation, 2016)
The professional performance of the teacher is a multidimensional construct. In the scientific literature and also in the assessment tools of academic activities in various universities there are multiple enumerations, more compressed or extended, of the qualities or characteristics of the effective teacher. This variety suggests, on one hand, the complexity of teaching, and, on the other hand, the absence of an integrative conceptual model of what success means in the professional academic environment. Therefore, the objective of the current research, carried out on a total of 612 subjects was to detect the factors associated with succes in the academic environment. The results represent a taxonomy of the fulfilment of the teaching performance and provides possible courses of action to take in order to optimize the teaching process.